Pengukuran Kinerja Pada Aplikasi Video Pembelajaran UMKM Berbasis Web Dengan Metode Pengujian Beban - Sentosa, Sucitra Aan; Subyantoro, Eko; Asrowardi, Imam (ROUTERS: Jurnal Sistem dan Teknologi Informasi, 2024)
In the digital era, the use of websites has become crucial for business development, including the SMEs learning application based on video developed by Siger Innovation Hub. Before the application can be widely used, it is important to conduct comprehensive testing to ensure a fast and stable response. This article measures website loading speed through performance testing. This testing identifies issues early on, providing information for improvements and enhancements before implementing the application on a larger scale. The chosen method is load testing, with the research phases following the Software Testing Life Cycle (STLC). The results obtained from the performance testing using the load testing method indicate that the website is capable of meeting the target response time (response time < 3000ms), achieving a peak throughput of 18/seconds, and having a maximum error rate of 0.50%. In conclusion, the website for the SMEs learning application with video media can operate optimally when tested with 1 to 100 users.